Tick-borne encephalitis in Europe and Russia: Review of pathogenesis, clinical features, therapy, and vaccines - Ruzek, Daniel; Avšič Županc, Tatjana; Borde, Johannes; Chrdle, Ales; Eyer, Ludek; Karganova, Galina; Kholodilov, Ivan; Knap, Nataša; Kozlovskaya, Liubov; Matveev, Andrey; Miller, Andrew D.; Osolodkin, Dmitry I.; et al. (Antiviral research, 2019)
Tick-borne encephalitis (TBE) is an illness caused by tick-borne encephalitis virus (TBEV) infection which is often limited to a febrile illness, but may lead to very aggressive downstream neurological manifestations. The disease is prevalent in forested areas of Europe and northeastern Asia, and is typically caused by infection involving one of three TBEV subtypes, namely the European (TBEV-Eu), the Siberian (TBEV-Sib), or the Far Eastern (TBEV-FE) subtypes. In addition to the three main TBEV subtypes, two other subtypes; i.e., the Baikalian (TBEV-Bkl) and the Himalayan subtype (TBEV-Him), have been described recently. In Europe, TBEV-Eu infection usually results in only mild TBE associated with a mortality rate of <2%. TBEV-Sib infection also results in a generally mild TBE associated with a non-paralytic febrile form of encephalitis, although there is a tendency towards persistent TBE caused by chronic viral infection. TBE-FE infection is considered to induce the most severe forms of TBE. Importantly though, viral subtype is not the sole determinant of TBE severity; both mild and severe cases of TBE are in fact associated with infection by any of the subtypes. In keeping with this observation, the overall TBE mortality rate in Russia is ∼2%, in spite of the fact that TBEV-Sib and TBEV-FE subtypes appear to be inducers of more severe TBE than TBEV-Eu. On the other hand, TBEV-Sib and TBEV-FE subtype infections in Russia are associated with essentially unique forms of TBE rarely seen elsewhere if at all, such as the hemorrhagic and chronic (progressive) forms of the disease. For post-exposure prophylaxis and TBE treatment in Russia and Kazakhstan, a specific anti-TBEV immunoglobulin is currently used with well-documented efficacy, but the use of specific TBEV immunoglobulins has been discontinued in Europe due to concerns regarding antibody-enhanced disease in naïve individuals. Therefore, new treatments are essential. This review summarizes available data on the pathogenesis and clinical features of TBE, plus different vaccine preparations available in Europe and Russia. In addition, new treatment possibilities, including small molecule drugs and experimental immunotherapies are reviewed. The authors caution that their descriptions of approved or experimental therapies should not be considered to be recommendations for patient care. •Tick-borne encephalitis (TBE) is an acute febrile viral illness with neurological manifestations.•No specific antivirals are approved for TBE therapy.•A number of nucleoside or non-nucleoside antivirals exhibit anti-TBE virus (TBEV) activity in vitro and in vivo.•Specific anti-TBEV immunoglobulin is used for post-exposure prophylaxis and TBE treatment in Russia but not in Europe.•TBE is preventable by effective vaccines but vaccination coverage remains low in many endemic countries.